Mutant of Aspergillus flavus producing more aflatoxin B2 than B1. - Papa, K E (1977)
A mutant of Aspergillus flavus having a high and relatively stable aflatoxin B2/B1 ratio was recovered after treatment with nitrosoguanidine.